PET Tracers for Imaging of ABC Transporters at the Blood-Brain Barrier: Principles and Strategies - Luurtsema, Gert; Elsinga, Philip; Dierckx, Rudi; Boellaard, Ronald; Waarde, Aren van (Current Pharmaceutical Design, 2016)
ABC transporters at the human blood-brain barrier protect the brain against the entry of harmful compounds but may also limit (or prevent) the cerebral entry of therapeutic drugs (e.g. anti-epileptics, antidepressants and antipsychotics). The efflux function of these transporters may be impaired in neurodegenerative disorders like Alzheimer and Parkinson disease. For such reasons, there is much interest in modulation of the efflux function of ABC transporters and in the monitoring of this function with positron emission tomography (PET). The efflux function of P-glycoprotein, an important member of the ABC transporter family, can be quantified with the PET tracer (R)-[11C]verapamil, but the lipophilicity of this probe and the formation of radioactive metabolites which enter the brain complicate such measurements considerably. (R)-[11C]verapamil is also not very suitable for the detection of P-gp upregulation, as may occur in epilepsy or drug resistance. Current radiochemical efforts are therefore focused on the development of PET probes with improved characteristics, for example; capability to detect both up- and down regulation of transporter function and expression, a better metabolic profile (no brain-entering metabolites), reduced lipophilicity and a longer physical half-life (labeling with 18F instead of 11C).
Keywords: efflux transporters